The search for new 4-amino-5-methyl-4H-1,2,4-triasole-3-thion derivatives with diuretic activity - T. V. Kravchenko (Zaporožskij Medicinskij Žurnal)
1,2,4-Triazole derivatives have been widely used in medical practice due to their wide spectrum of biological activities and low toxicity, as they have 1,2,4-triazole cycle in their structure. That makes 1,2,4-triazole derivatives a very promising and attractive class of organic compounds in research of their physical and chemical properties, and biological activity determining. In order to find new substances with potential biological activity 20 new compounds of 4-amino-5-methyl-4H-1,2,4-tiazole-3-thion derivatives were synthesized, which have never been described in literature before.